THE ROLE OF TRAINING AND DEVELOPMENT IN IMPROVING ECONOMIC COMPETITIVENESS - Fittry Megasari Sijabat (CV. Adiba Aisha Amira, 2024)
This research examines the important role of Human Resource (HR) training and development in improving economic competitiveness. In the era of globalisation and rapid technological advancement, the quality of human resources is a key factor in determining the competitive advantage of a country or organisation. This study uses the literature analysis method. The results show that effective HR training and development can increase productivity, encourage innovation, and improve adaptability to market changes. Furthermore, it was found that sustainable HR development contributes to the reduction of skills gaps, improvement of workers' quality of life, and strengthening of strategic economic sectors. In conclusion, investment in training and development is a critical strategy in improving economic competitiveness.